2021
DOI: 10.1371/journal.pone.0256997
|View full text |Cite
|
Sign up to set email alerts
|

Can co-authorship networks be used to predict author research impact? A machine-learning based analysis within the field of degenerative cervical myelopathy research

Abstract: Introduction Degenerative Cervical Myelopathy (DCM) is a common and disabling condition, with a relatively modest research capacity. In order to accelerate knowledge discovery, the AO Spine RECODE-DCM project has recently established the top priorities for DCM research. Uptake of these priorities within the research community will require their effective dissemination, which can be supported by identifying key opinion leaders (KOLs). In this paper, we aim to identify KOLs using artificial intelligence. We prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…This appears consistent with definitions used for existing conditions and based on the process, suitable for inclusion within ICD. 30 Whilst there were significant strengths to the process, including its global 31 multistakeholder perspective and iterative approach, an important limitation to acknowledge is that the term 'DCM' was used from the outset, for example within the supporting and explanatory information, as well as the project title AO Spine RECODE-DCM, as having a term to identify the condition was unavoidable. The inclusion of contrasting terms, alongside their prominence within voting and discussion, is a reassuring suggestion at least, that this did not confer an unconscious bias.…”
Section: Discussionmentioning
confidence: 99%
“…This appears consistent with definitions used for existing conditions and based on the process, suitable for inclusion within ICD. 30 Whilst there were significant strengths to the process, including its global 31 multistakeholder perspective and iterative approach, an important limitation to acknowledge is that the term 'DCM' was used from the outset, for example within the supporting and explanatory information, as well as the project title AO Spine RECODE-DCM, as having a term to identify the condition was unavoidable. The inclusion of contrasting terms, alongside their prominence within voting and discussion, is a reassuring suggestion at least, that this did not confer an unconscious bias.…”
Section: Discussionmentioning
confidence: 99%
“…Countries were further categorised as higher-income countries or not, using the World Bank (worldbank.org) classification (22 October 2020). In addition, we and others have identified that DCM research is largely derived from two geographical clusters: North America (Canada and the USA) and East Asia (Japan, Korea and China) 17 18. To explore a relationship between research activity and KT, participants were also defined by whether they reside or practice within a research cluster or not.…”
Section: Methodsmentioning
confidence: 99%
“…We identified network opinion leaders through the mutual influence and interaction between users. The H-index, proposed in 2005, was chosen as the most suitable surrogate impact metric [70], which can also be used to describe and assess the magnitude of users' influence in the network and the amount of output [71]. The degree of attention, interaction, and conversation content obtained through user's posting of posts were used as the basis for measuring the influence of the poster [72], which was specifically reflected in the number of likes and comments on the post.…”
Section: Identification and Measurement Of Opinion Leadersmentioning
confidence: 99%